Assessment and analysis of the application of sewage treatment technologies in Poland - Agata Mesjasz-Lech; Wioletta M. Bajdur (European Regional Science Association (ERSA), 2013)
Environmental pollution is a serious problem in highly industrialized countries, as it may pose a threat to the human health and life. For these reasons, entities responsible for polluting the environment and its natural resources undertake pro-environmental actions that involve reduction of the negative impact of the activities of human beings and businesses on the environment. Such activities are aimed at the application of low and no-waste technologies. Unfortunately, it is impossible to completely eliminate pollution from the human activity. This article focuses on sewage treatment technologies, the purpose of which is to eliminate the already existing pollution. Therefore, the analyses were limited to water and sewage treatment technologies, as the growing demand for water, its constantly deteriorating purity and requirements as regards its quality, force changes in the water resources management system. In various provinces in Poland, environmental protection is being implemented more or less successfully. It is necessary to apply the principles of environmental protection to the human behaviour and activity of business entities, because there are more and more activities particularly harmful to the natural environment. The implemented modern technologies aimed at the elimination of (or eliminating) the negative impact of human and business activities on the natural environment, are bringing the desired results as far as the protection of individual natural resources is concerned. One of the fundamental imperfections of the market is a lack of environmental resources, such as air or water. Inability to define the economic value of the natural resources results in their constant, excessive exploitation and degradation. However, the growing awareness of the environmental issue in Poland is resulting in the application of technologies that protect individual natural resources. This paper attempts to determine the measures of pro-environmental activities in the scope of sewage treatment, undertaken on the territory of individual provinces, and to classify the provinces in accordance with the achieved level of application of sewage treatment technologies. For this purpose one has used the numerical taxonomy methods, and in particular the methods of linear ordering of objects (that involve projection of the objects from a multidimensional space of features onto a straight line), called the methods of multidimensional comparative analysis. The measures were designed based on available statistical data from 2011. The purpose of this article is to find out which provinces are similar to each other in terms of the application of sewage treatment technologies, and to find a province that has managed to achieve the best results in this regard.
Keywords: F64; 330; Keywords: environmental pollution; sewage treatment; multidimensional comparative analysis